Environmental Regulation and High-quality Economic Development in the Yangtze River Delta Urban Agglomeration - Liu, Renming (International Journal of Applied Research in Management and Economics, 2023)
China's economy has been under tremendous pressure due to the decoupling from the United States, leading to a prolonged economic downturn. In response, the Political Bureau of the CPC Central Committee has introduced the concept of “internal circulation”, aiming to stimulate domestic demand and provide new momentum for economic growth. This study examines the relationship between high-quality economic development and environmental regulations by analyzing panel data from 33 cities over an 18-year period. The paper constructs comprehensive indexes for measuring high-quality economic growth and environmental regulation using the entropy method, followed by the variance inflation factor test to detect multicollinearity. The implications of this study are significant for policymakers who strive to achieve high-quality economic development with environmental sustainability. The results indicate that environmental regulation can act as a new driver of high-quality economic growth, emphasizing the need to continue strengthening environmental regulation. Therefore, we recommend that the policymakers should prioritize environmental protection in policy-making, striving to achieve a balance between economic growth and environmental sustainability.